Playback-theatre in the system of socialization and re-socialization of personality - Dergach, M. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article reveals the peculiarities of playback theater as a psychodramatic technique, analyzes the current practice of using playback theater in the system of socialization and re-socialization. The author found that socialization, as a necessary process for interaction with the outside world, is manifested in the assimilation and appropriation of social experience for the purpose of productive functioning in it and to construct an image of the common and own world (as a part of the common), which allows a person to live a life while preserving individuality. and creatively influence the world. Within this provision, playback theater should be regarded as a technology of the paratheater system of dramatherapy, which is relevant at any stage of the socialization of the individual or as a means in the mechanisms of socialization. Playback theater contributes to the development of tolerance for social differences, the acceptance of another with all its features, values. Thanks to him, we learn to listen to understand others, because in the performance the main thing is the story of the viewer, the realization of which is impossible in reality without careful perception. The author has found that playback theater as a paratheater system of drama is a rather interesting and important means of socialization and re-socialization of the personality, it can be used in any group of people to solve problems of a wide range. The article describes in detail the content of the playback theater application, namely: social integration of individual subgroups into society; social and psychological adaptation of personality; social-psychological and therapeutic support for people who are in emotional and psychological state; creation of a more favorable social and psychological climate for the team; social and psychological support in complex events; development of personal qualities of children in educational institutions; social and psychological support of people in recreational activities; playback theater as a means of creating space for social networking. Prospects for further research on the topic of the article are to study the attitude of the audience to the performances of the playback theater, the search for the means of expression of the actors, the impact of playback on the children's audience.
Keywords: psychodrama; paratheatrical system; playback-theatre; socialization; re-socialization; personality